Т. 20 : Издания, вышедшие из печати в 1975 г.; Библиография изданий Академии наук СССР - Васильева В. А.; Воронова М. В.; Купатадзе Т. М.; Чуркина Л. А.; Шигаева Ж. Г.; Петровская М. В. (1978, 1978)
Исключено из фонда НТБ ТПУ